Ethical Decision-Making Approaches of Companies’ Financial Managers - Gholamhossein Mahdavi (Shahid Bahonar University of Kerman, 2012)
The main objective of this research is to identify the financial managers' ethical decision-making approaches of companies listed in Tehran Stock Exchange and different factors affecting them. To achieve this aim, 12 hypotheses have been developed. The aim of the first six hypotheses is to investigate different ethical decision-making approaches, namely utilitarianism, hermeneutical, nonethical, religious, deontological, and pragmatism. The next six hypotheses are to identify the probable factors affecting these approaches. The data required for the statistical analysis of research hypotheses was obtained from 63 companies using a 24-item questionnaire. The results from testing the first set of hypotheses indicated that financial managers of companies listed in Tehran Stock Exchange believed in utilitarian, religious, and deontological but they did not believe in hermeneutical, nonethical and pragmatic approaches. Moreover, in the opinion of financial managers, utilitarianism was the strongest ethical decision-making approach and pragmatism was the weakest one. Finally, the statistical analysis of the next six hypotheses showed that, except for the effect of variable “age ”on the religious approach, the other hypothesized effects were statistically insignificant.